Evaluation of E-Service Quality Dimensions in Shopee Indonesia User Reviews - Desty Hapsari Kirana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the dimensions of e-service quality reflected in user reviews of the Shopee Indonesia application and explores how these dimensions are associated with user ratings. The study employed a descriptive quantitative approach using secondary data in the form of 67,600 user reviews collected between January 24, 2026 and April 13, 2026. The review content was analyzed through deductive content analysis by classifying user expressions into five dimensions of e-service quality, namely efficiency/system availability, fulfillment/reliability, responsiveness, security/assurance, and price/value support. In addition, user ratings were grouped into three categories—negative (1–2), neutral (3), and positive (4–5)—to examine the distribution of evaluations across the identified dimensions. The findings reveal that Fulfillment/Reliability and Efficiency/System Availability are the two most dominant dimensions in Shopee user reviews. Among these, Fulfillment/Reliability is the dimension most strongly associated with low ratings, indicating that issues related to delivery, orders, packages, couriers, and service timeliness are the main sources of user dissatisfaction. Meanwhile, Price/Value Support is more frequently associated with positive evaluations, suggesting that promotions, discounts, vouchers, and affordability remain important strengths of the platform. Overall, the results indicate that users evaluate marketplace service quality not only in terms of products offered, but also in terms of service reliability, platform performance, and responsiveness. These findings provide practical insights for e-commerce platform managers in identifying service areas that should be prioritized for improvement.